PENERAPAN ALGORITMA BRUTE FORCE PADA APLIKASI PENERJEMAH BAHASA INDONESIA - BAHASA MANDAILING BERBASIS MOBILE - Ayu Sahriani Dalimunthe; Mhd. Furqan; Abdul Halim Hasugian (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Language is a means to communicate. Knowledge of language is very important because in a conversation or conversation requires a language. In Indonesia, there are many various regional languages, including the Mandailing language. Mandailing language is one of the regional languages in South Tapanuli, North Sumatra. The use of regional languages has experienced a lot of decline in use in the language of everyday communication. Preserving regional languages is very necessary in the midst of increasingly rapid technological developments. Dictionary media can be a solution to introduce various regional languages in Indonesia. In this study, the design and development of the Indonesian-Mandailing Translator Application was carried out with the application of the Mobile-based Brute Force Algorithm. This application was built using Android Studio software using the Java programming language and XML. The database used to store data for the Batak Mandailing-Indonesian translator is a SQLite database so that the application can be used offline. Applications that are designed in a user friendly manner can perform the search function for Indonesian-Mandailing and Mandailing-Indonesian Vocabulary, making it easier for users to operate them. Keywords: Mandailing language, dictionary, Brute Force Algorithm, Android                  Application Abstrak: Bahasa merupakan sarana untuk berkomunikasi. Pengetahuan bahasa sangatlah penting karena dalam sebuah percakapan atau pembicaraan memerlukan sebuah bahasa. Di Indonesia ada banyak beragam bahasa daerah diantaranya adalah Bahasa Mandailing. Bahasa Mandailing merupakan salah satu bahasa daerah bagian Tapanuli Selatan, Sumatera Utara. Penggunaan bahasa daerah telah mengalami banyak penurunan penggunaan dalam bahasa komunikasi sehari-hari. Melestarikan bahasa daerah sangat perlu ditengah perkembangan teknologi yang semakin pesat. Media kamus dapat menjadi solusi untuk mengenalkan beragam bahasa daerah yang ada di Indonesia. Dalam penelitian ini dilakukan perancangan dan membangun Aplikasi Penerjemah Bahasa Indonesia-Mandailing dengan penerapan Algoritma Brute Force berbasis mobile. Aplikasi ini dibangun menggunakan perangkat lunak Android Studio menggunakan bahasa pemrograman Java dan XML. Database yang digunakan untuk menyimpan data penerjemah bahasa Batak Mandailing-Indonesia adalah SQLite database sehingga aplikasi dapat digunakan secara offline. Aplikasi yang dirancang secara user friendly dapat melakukan fungsi pencarian Kosa kata Bahasa Indonesia - Mandailing dan Mandailing - Indonesia sehingga memudahkan para pengguna dalam mengoperasikannya. Kata kunci: Bahasa Mandailing, Kamus, Aplikasi Android